Slowly progressive aphasia followed by Alzheimer' s dementia: a case report - Silmara A. V. de Oliveira; Maria Júlia M. de O. Castro; Paulo Rogério M. Bittencourt (Arquivos de Neuro-Psiquiatria)
Slowly progressive aphasia has been found in 8 published cases, 2 of whom progressed over a period of years to generalized dementia. Positron emission tomography demonstrated decreased glucose metabolism in the left perisylvian region in 2 cases. We describe a patient who had slowly progressive aphasia and developed generalized Alzheimer's dementia 7 years after presentation. There was no clinical or laboratory evidence of concomitant disease. Computerized tomography showed generalized atrophy more marked on the left perisylvian region late in the disease, when EEG showed generalized slowing more marked on the same area. Slowly progressive aphasia of old age should be considered a separate entity until further studies elucidate its relation to Alzheimer's dementia.